2012
DOI: 10.1016/j.dci.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

MIF from mussel: Coding sequence, phylogeny, polymorphism, 3D model and regulation of expression

Abstract: a b s t r a c tThree macrophage migration inhibitory factor (MIF)-related sequences were identified from a Mytilus galloprovincialis EST library. The consensus sequence included a 5 0 -UTR of 32 nucleotides, the complete ORF of 345 nucleotides, and a 3 0 -UTR of 349 nucleotides. As for other MIFs, M. galloprovincialis ORF does not include any signal or C-terminus extensions. The translated sequence of 115 amino acids possesses a molecular mass of 12,681.4, a pI of 6.27 and a stability index of 21.48. Its 3D st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Two other inflammatory cytokines have been identified by similarity searches in bivalves: the macrophage migration inhibitory factor (MIF), which is present with at least three distinct gene products in M. galloprovincialis [213], and the allograft 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 inflammatory factor (AIF), able to stimulate the phagocytic activity of granulocytes, which has been identified in different bivalve species [214e216] and is now confirmed also in M. galloprovincialis.…”
Section: Modulators Of the Immune Responsementioning
confidence: 99%
“…Two other inflammatory cytokines have been identified by similarity searches in bivalves: the macrophage migration inhibitory factor (MIF), which is present with at least three distinct gene products in M. galloprovincialis [213], and the allograft 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 inflammatory factor (AIF), able to stimulate the phagocytic activity of granulocytes, which has been identified in different bivalve species [214e216] and is now confirmed also in M. galloprovincialis.…”
Section: Modulators Of the Immune Responsementioning
confidence: 99%
“…In this study, a macrophage migration inhibitory factor (ADU19847) was identified and suggested to be a proinflammatory cytokine with the ability to induce various immunomodulatory and proinflammatory responses in vertebrates and invertebrates [143][144][145]. Transcripts of MIF have been shown to be expressed and regulated in response to microbial stimuli in different organs including pallial or digestive tissues in mussels [146] and oysters [147].…”
Section: Immune Activation and Cell Signalingmentioning
confidence: 99%
“…Previous researches have demonstrated a great diversity in the immune responses of mussels, both at inter and intra-population level, in relation to the microorganism to which they are exposed . In mussel M. galloprovincialis, widely used as an experimental model species of bacterial infection, it has been demonstrated a recruitment of hemocytes containing antimicrobial peptides (AMPs), including mytilins, towards the site of injection within hours following bacterial challenge, along with a prominent role of mytilins in killing intracellular bacteria after phagocytosis (Mitta et al, 2000a;Parisi et al, 2012;Sonthi et al, 2012). Furthermore, an increase of soluble AMPs in the plasma of mussels suggests the occurrence of secondary systemic responses to microbial challenges (Mitta et al, 2000b;Toubiana et al, 2014).…”
Section: Discussionmentioning
confidence: 99%